A comparative study of hypolipidemic effect of atorvastatin and Coriandrum sativum in triton-induced hyperlipidemic albino rat model - M., Pooja; A., Puneeth (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Hyperlipidemia is the main factor responsible for coronary artery disease. Atorvastatin commonly used, as a competitive inhibitor of HMG-Co-A reductase, is known to reduce LDL and triglyceride levels and increase HDL levels. Coriandrum sativum (Coriander) belongs to the Apiaceae family and has hypolipidemic, antidiabetic, and antioxidant properties. Triton WR1339 has been used by several studies to induce hypercholesterolemia in animals which acts on both the synthesis and excretory phase. This study aimed to compare the hypolipidemic effect of Coriandrum sativum and atorvastatin in triton-induced hyperlipidemic rats. Methods: Following approval from the Institutional Animal Ethics committee, 36 Wistar albino rats were divided into 6 groups of 6 animals each. Triton 200mg IP was administered to all the groups except Group 1 (control). Groups 3 and 4 received Coriander extract 300mg/kg and Atorvastatin 80mg/kg orally with Triton. Groups 5 and 6 received Coriander extract and Atorvastatin respectively 22 hours later. Lipid profile was estimated 24 hours before, 24 and 48 hours after administering Triton. Results: In the synthesis phase, there is a statistically significant increase in the lipid levels in Groups 2, 5, and 6 compared to Groups 3 and, 4 indicating hypolipidemic effects of both Coriander extract and Atorvastatin. In the excretory phase, all groups have shown a decrease in lipid levels but a decrease in total cholesterol level in Group 5 compared to Group 3 was significant. Conclusions: Atorvastatin and Coriander extract both affect the lipid levels in the synthesis and excretory phase. Even though coriander cannot replace atorvastatin in the management of hyperlipidemia, it can be used as an adjuvant to atorvastatin to reduce the cost effects and adverse reactions caused by allopathic medicines.